Cardiac sympathetic denervation could be associated with dysphagia in Parkinson's disease - Youn, Jinyoung; Umemoto, George; Oh, Eungseok; Park, Jinse; Jang, Wooyoung; Oh, Yoon-Sang; Kim, Hee-Tae; Cho, Jin Whan; Fujioka, Shinsuke; Tsuboi, Yoshio (Frontiers in Neurology, 2022)
Background Dysphagia is an important non-motor symptom that is closely associated with quality of living and mortality in Parkinson's disease (PD). However, the pathophysiology of dysphagia in PD remains inconclusive. We tried to confirm whether the occurrence of dysphagia could be related to sympathetic degeneration using cardiac 123I-metaiodobenzylguanidine (MIBG) scintigraphy. Methods We prospectively recruited 27 PD patients and classified them into two groups (PD with dysphagia vs. PD without dysphagia) by Swallowing Disturbance Questionnaire (SDQ) score and compared the clinical characteristics, videofluoroscopic swallowing study (VFSS) findings and parameters from cardiac MIBG scintigraphy. Results The mean early and late H/M ratios were significantly lower in the PD with dysphagia group than those in the PD without dysphagia group (1.39 ± 0.21 vs. 1.86 ± 0.21, p < 0.01; 1.26 ± 0.18 vs. 1.82 ± 0.29, p < 0.01). In the correlation analysis, both the early and late H/M ratios were negatively correlated with the SDQ score and total VDS score (r = −0.65, p < 0.01; r = −0.53, p < 0.01; r = −0.65, p < 0.01, r = −0.58, p < 0.01). Conclusion We confirmed that cardiac sympathetic denervation might be associated with the presence and severity of dysphagia. This finding indicates that dysphagia in PD could be associated with a nondopaminergic mechanism.